Assessment of Vitamin A (VA) Total Body Stores (TBS) Using Dried Derum Spots (DSS). (29th May 2020) - Lietz, Georg; Oxley, Anthony; Engle-Stone, Reina; Miller, Jody; Reario, Dolly; Stormer, Ame; Capanzana, Mario; Cabanilla, Carl; Haskell, Marjorie
Abstract: Objectives: The retinol isotope dilution method has been successfully applied to assess the efficacy of VA interventions in low and middle-income countries. However, the current method is limited in its applicability because it relies on keeping serum samples in the cold chain. To overcome that limitation, we assessed the feasibility of using DSS for assessing TBS in Filipino children 12–18 months of age. Methods: Serum (40 µL) from Filipino children, who had received an oral dose of [, 13 C10 ]-retinyl acetate was spotted and dried on Whatman 903 cards then stored at −20°C before shipment at room temperature; aliquots of liquid serum were kept frozen at −80°C until analysis. DSS and liquid serum were extracted by established methods and then analysed by LC-MS/MS to quantify the [, 13 C]/[, 12 C] retinol ratio and TBS. Results: Mean ± SD TBS of 57 Filipino infants aged 12–18 mo were 507.6 ± 185.8 µmol and 495.5 ± 170.1 µmol from either serum or DSS samples, respectively. Comparison of methods using Bland-Altman analysis indicated agreement between both methods with an intra-individual mean difference for TBS of 22.1 µmol (4.5%). Conclusions: TBS can be determined using serum spot samples in field settings, thus reducing the costs and limitations of shipping serum samples on dry ice and reducing the need for −80C storage in field stations. Funding Sources: Medical Research Council UK; Bill and Melinda Gates Foundation.